Malay narratives in Nanyang travel - Ser, Wue Hiong; Ng, Chwee Fang (Universiti Putra Malaysia Press, 2020)
“Nanyang” 南洋was a general term used by the Chinese for Southeast Asia before World War II. After the 19th century, the Chinese moved to Nanyang in succession. Located at the centre of “Nanyang”, the Malay Peninsula and Singapore became the gathering place of the Chinese at that time and they unexpectedly encountered the indigenous Malay civilisation, thus arousing cultural interaction and immersion. In the 1920s and 1930s, a large number of Chinese literati came to the south for various purposes such as seeking relatives and friends, travelling, investigating, or settling down for a long time, and they recorded the experiences of what they saw and heard in Nanyang in travel records or books. The “Nanyang Youji” 南洋游记 (Nanyang Travels) mainly recorded the customs and anecdotes of the Nanyang society. It is rich in content, diverse in subject matter, and large in volume. It also has a unique writing style, with great literary, historical, and even cultural anthropology value. Although the content of “Nanyang Youji” is mainly based on Chinese society and culture, many of them also contain records of the Malay customs and culture that the author personally witnessed which are thus, very precious. This article reviews several “Nanyang Youji” travel records to gain an insight into the Malay society and the Chinese-Malay cultural interaction from the perspective of the early Nanyang travellers.